(untitled) - Finnie, Rachel (Kennington, Oxford, 2002)
Link is a comprehensive course that offers a clear, balanced approach to learning English. It provides an attractive and motivating link between elementary and advanced levels.
Keywords: English language,English language; Study and teaching